Genetic variants in the PSMA6, PSMC6 and PSMA3 genes associated with childhood asthma in Latvian and Taiwanese populations - Paramonova, N.; Wu, L.ShiShin; Rumba-Rozenfelde, I.; Wang, J.Y.; Sjakste, N.; Sjakste, T. (Вiopolymers and Cell, 2014)
Proteasomes mediate functional realization of signaling proteins implicated in asthma pathogenesis. Aim. To evaluate main and sex-specific association between the PSMA6, PSMC6 and PSMA3 proteasomal genes variations and childhood asthma in Latvians and Taiwanese. Methods. SNPs rs2277460, rs1048990, rs2295826, rs2295827 and rs2348071 were genotyped in 102 Latvian and 159 Taiwanese cases for comparison with genetic diversity in populations (191 and 1097 subjects respectively). Results. Haplotype CGACG showed strong (P < 0.0001) association with asthma risk in both populations. All loci heterozygous genotypes and haplotype CCGTA were identified as asthma risk factors in Latvians; rs1048990 and rs2348071 GG homozygotes and rs2295826 and rs2295827 heterozygotes showed asthma risk and protective effect in Taiwanese females respectively. The multi locus genotypes homozygous for alleles being common in Latvian population were identified as protective in Latvians and disease susceptible in Taiwanese. Conclusions. Our results suggest an association of the 14q13-23 proteasomal genes polymorphisms with the childhood asthma in Latvians and Taiwanese and high-light risk and/or protective factors being the same or different between the populations. Протеасоми опосередковують реалізацію функцій сигнальних білків, залучених до патогенезу бронхіальної астми. Мета. Оцінити загальну і залежну від статі асоціацію варіацій протеасомних генів PSMA6, PSMC6 і PSMA3 з бронхіальною астмою у дітей із Латвії і Тайваня. Mетоди. Однонуклеотидні поліморфізми rs2277460, rs1048990, rs2295826, rs2295827 і rs2348071 генотиповано у 102 хворих з Латвії і 159 – з Тайваня. Для порівняння взято контрольні групи, які представляють генетичне різноманіття в популяціях: 191 латвійських і 1097 тайваньських зразків. Результати. Гаплотип CGACG виявився тісно (P < 0.0001) асоційованим з ризиком розвитку астми в обох популяціях. Гетерозиготні генотипи за всіма локусами і гаплотип CCGTA ідентифіковано як фактор ризику для розвитку астми у жителів Латвії. Гомозиготи GG по rs1048990 і rs2348071 пов’язані з ризиком, а гетерозиготи по rs2295826 і rs2295827 проявляють захисний ефект з-поміж тайваньських жінок. Багатолокусні генотипи, гомозиготні за розповсюдженими в Латвії алелями, виявилися захисними для жителів Латвії, але пов’язаними з ризиком захворювання серед тайваньців. Висновки. Наші результати вказують на асоціацію поліморфізмів протеасомних генів локусу 14q13-23 з бронхіальною астмою серед дітей у латвійській і тайваньській популяціях, асоціація може бути пов’язана як з ризиком захворювання, так і з захисним ефектом. За даною ознакою популяції можуть різнитися або не різнитися. Протеасомы опосредуют реализацию функций сигнальных белков, вовлеченных в патогенез бронхиальной астмы. Цель. Оценить общую и зависимую от пола ассоциацию вариаций протеасомных генов PSMA6, PSMC6 и PSMA3 с бронхиальной астмой у детей из Латвии и Тайваня. Mетоды. Однонуклеотидные полиморфизмы rs2277460, rs1048990, rs2295826, rs2295827 и rs2348071 генотипированы у 102 больных из Латвии и 159 – из Тайваня. Для сравнения взяты контрольные группы, представляющие генетическое разнообразие в популяциях: 191 латвийских и 1097 тайваньских образцов. Результаты. Гаплотип CGACG оказался тесно (P < 0.0001) ассоциированным с риском развития астмы в обеих популяциях. Гетерозиготные генотипы по всем локусам и гаплотип CCGTA идентифицированы как фактор риска для развития астмы у жителей Латвии. Гомозиготы GG по rs1048990 и rs2348071 связаны с риском, а гетерозиготы по rs2295826 и rs2295827 проявляют защитный эффект среди тайваньских женщин. Многолокусные генотипы, гомозиготные по распространенным в Латвии аллелям, оказались защитными для жителей Латвии, но связанными с риском заболевания среди тайваньцев. Выводы. Наши результаты указывают на ассоциацию полиморфизмов протеасомных генов локуса 14q13-23 с бронхиальной астмой среди детей в латвийской и тайваньской популяциях, ассоциация может быть связана как с риском заболевания, так и с защитным эффектом. По данному признаку популяции могут отличаться или не отличаться.